THE EFFECT OF GROSS REGIONAL DOMESTIC PRODUCT, TOTAL OF LABOR, AND LOCAL GOVERMENT EXPENDITURE TOWARDS POVERTY LEVEL OF DISTRICT/TOWN IN WEST KALIMANTAN PROVINCE YEAR 2011-2015 - B1011131093, ZULFACHRI ADJIE PRASETYA (Jurnal Pembangunan dan Pemerataan, 2017)
This study aims to examine and analyze the effect of GRDP (gross regional domestic product), total of labor, and local government expenditure on district/town poverty level in West Kalimantan Province with independent variable (X) that is gross regional domestic product, total of labor, and local government expenditure on the dependent variable (Y) which is the level of poverty. This type of research is quantitative data collecting using literature books, journals or sources related to the problem under study. Analysis of this research data using multiple linear analysis technique.The results of this study indicate the hypothesis that the gross regional domestic product has a negative and insignificant effect on the level of poverty of districts/town in West Kalimantan Province, total of labor has a negative and significant effect on the level of poverty of districts in West Kalimantan Province, and local government expenditure has a positive effect and insignificant to district level poverty in West Kalimantan Province.Keywords : Gross Regional Domestic Product, Total of Labor, Local Government Expenditure and Poverty Level